Characteristics and prognosis of pneumococcal endocarditis: a case–control study. (June 2016) - Daudin, M.; Tattevin, P.; Lelong, B.; Flecher, E.; Lavoué, S.; Piau, C.; Ingels, A.; Chapron, A.; Daubert, J.-C.; Revest, M.
Abstract: Case series have suggested that pneumococcal endocarditis is a rare disease, mostly reported in patients with co-morbidities but no underlying valve disease, with a rapid progression to heart failure, and high mortality. We performed a case–control study of 28 patients with pneumococcal endocarditis (cases), and 56 patients with non-pneumococcal endocarditis (controls), not matched for sex and age, during the years 1991–2013, in one referral centre. Alcoholism (39.3% versus 10.7%; p <0.01), smoking (60.7% versus 21.4%; p <0.01), the absence of previously known valve disease (82.1% versus 60.7%; p 0.047), heart failure (64.3% versus 23.2%; p <0.01) and shock (53.6% versus 23.2%; p <0.01) were more common in pneumococcal than in non-pneumococcal endocarditis. Cardiac surgery was required in 64.3% of patients with pneumococcal endocarditis, much earlier than in patients with non-pneumococcal endocarditis (mean time from symptom onset, 14.1 ± 18.2 versus 69.0 ± 61.1 days). In-hospital mortality rates were similar (7.1% versus 12.5%). Streptococcus pneumoniae causes rapidly progressive endocarditis requiring life-saving early cardiac surgery in most cases.